Fiction Theory in Antonio Muñoz Molina’s "La poseída" - Rivas Hernández, Ascensión (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This paper analyzes the resources that Muñoz Molina uses in «La poseída» to transform a real event into a fictional one. The most important is the choice of the point of view. This way, the focus on a timid character of feverish imagination, turns a vulgar fact, due to its unfortunate repetition, into an adventure full of misunderstandings into whose traps the reader falls down. In order to achieve that, the author makes use of free indirect speech, which shows the character´s internal states and delves into the delirium of the personage. Opposite to it, the implied author slides indications that insinuate another sense to the history, whilst the vision of the personage is credibly organized. In addition, the accumulation of temporary references shows a psychological time that makes the surprise of the end of the history more urgent and singular, as it finally turns out completely opposite to the way the facts are presented.